90‐day oral toxicity study in rats of a protein‐rich powder derived from Xanthobacter sp. SoF1 - Choi, Bean; Glávits, Róbert; Murbach, Timothy S.; Endres, John R.; Hirka, Gábor; Szakonyiné, Ilona Pasics (Journal of applied toxicology, 2024)
Xanthobacter sp. SoF1 (SoF1) is an autotrophic hydrogen‐oxidizing bacteria that produces protein‐rich biomass and has potential to be an alternative protein source that is more environmentally sustainable than animal and plant derived proteins. A protein‐rich powder derived from SoF1 was the test material in a 90‐day repeated‐dose oral toxicity study to explore major toxic effects, demonstrate target organs, and provide an estimate of a no‐observed‐adverse‐effect level (NOAEL). Daily doses of 0 (vehicle only), 375, 750, and 1500 mg/kg bw/day of the test material were administered by gavage to 10 Han:WIST rats/sex/group. An additional group was administered 1290 mg/kg bw/day whey protein concentrate as positive control. No treatment‐related adverse effects were observed, and no target organs were determined after 90/91 days of consecutive administration of the test item. A NOAEL of 1500 mg/kg bw/day was determined. A 90‐day repeated‐dose oral toxicity study was conducted to assess the subchronic toxicity of a microbial protein powder derived from Xanthobacter sp. SoF1. Daily doses of 0 (vehicle only), 375, 750, and 1500 mg/kg bw/day of the test material and 1290 mg/kg whey protein concentrate as a positive control were administered by gavage to 10 Han:WIST rats/sex/group. A no‐observed‐adverse‐effect‐level of 1500 mg/kg bw/day was determined.